Long-acting corrosion-resistant polyaspartate polyurea composite coating and preparation method and application thereof

CN120041064BActive Publication Date: 2026-10-27SUN YAT SEN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510225977.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2026-10-27
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

但是其整体涂料制备工艺步骤极为复杂,工艺条件苛刻,不仅需要对氧化石墨烯进行改性,还需要将双酚F型环氧树脂和稳定型转锈剂进行复配对聚脲防腐涂层进行改性以提升聚脲防腐涂层与金属基材间的附着力

Benefits of technology

[0030]本发明提供一种天门冬氨酸酯聚脲涂料制备方法,以多巴胺-盐酸改性的氧化石墨烯为填料,提高形成涂层的力学性能和耐蚀性能;其中多巴胺-盐酸作为改性剂能提升氧化石墨烯纳米片与聚天门冬氨酸酯聚脲的相容性,同时多巴胺在氧化石墨烯表面发生自聚合,形成具有良好粘附性的聚多巴胺层,能够修复氧化石墨烯纳米片的表面缺陷,提升涂层致密性,延长腐蚀介质到达金属表面的时间,还能提高涂层与金属基体间的附着力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120041064B_ABST
    Figure CN120041064B_ABST
Patent Text Reader

Abstract

The application discloses a long-acting corrosion-resistant polyaspartic ester polyurea composite coating and a preparation method and application thereof, and relates to the technical field of corrosion and protection coating.The two-dimensional sheet composite material is prepared by graphene oxide and dopamine.In the application, dopamine is self-polymerized on the surface of graphene oxide to form a polydopamine layer with good adhesion, surface defects of the graphene oxide nanosheet are repaired, the compatibility of the graphene oxide nanosheet and the polyaspartic ester polyurea is improved, the dispersibility of the composite material is improved, the physical barrier performance of the coating is enhanced, internal defects of the coating are reduced, the compactness of the coating is improved, and the time for corrosion medium to reach the metal surface is prolonged, so that the polyaspartic ester polyurea composite coating finally exhibits excellent mechanical properties and corrosion resistance, and has an important application prospect in the field of corrosion and protection of marine equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of corrosion and protective coating technology, specifically relating to a long-lasting corrosion-resistant polyaspartic acid ester polyurea composite coating, its preparation method, and its application. Background Technology

[0002] The development and utilization of various marine resources are the cornerstone of the rapid development of the national marine economy, and the long-term and stable service of marine engineering equipment and vessels is the guarantee for marine resource development. However, marine engineering equipment operates under harsh environments of high salinity, high humidity, high temperature, and strong ultraviolet radiation for extended periods. Corrosion and its coupled damage are among the main factors causing reduced lifespan and safety accidents. Practice has proven that organic coatings play an important role in protecting marine engineering equipment and extending its service life; among them, polyaspartic acid ester polyurea coatings are environmentally friendly and have good corrosion resistance, and are widely used in the protection of marine engineering equipment. However, during the curing and service process, the coating can develop pores and cracks. In practical applications, under these conditions, the penetration of corrosive media can accelerate the deterioration of metal properties, thereby shortening the service life of the equipment. Therefore, how to reduce internal defects in the coating, improve its mechanical properties and corrosion resistance, and thus extend the service life of marine engineering equipment is a technical problem that urgently needs to be solved by technicians in the field of corrosion and protection.

[0003] To address the defects in polyaspartic acid ester polyurea coatings during curing and service, current solutions typically involve modifying the coating by adding nanofillers. However, not all nanofillers exhibit good compatibility with polyaspartic acid ester polyurea; therefore, directly adding nanofillers may disrupt the internal structural integrity of the coating, leading to a decrease in its overall protective performance. Two-dimensional graphene oxide sheets are widely used to reduce internal defects in coatings and block the penetration of corrosive media. However, the surface of graphene oxide sheets often contains defects, and graphene oxide, being an inorganic material, exhibits poor compatibility with polyaspartic acid ester polyurea, resulting in weak filler / resin interfaces. Therefore, if surface defects in graphene oxide can be repaired simultaneously while improving the compatibility between the filler and polyaspartic acid ester polyurea, it is expected to significantly improve the mechanical and corrosion resistance properties of the coating and extend its service life.

[0004] Patent CN118931250A discloses a modified graphene oxide and polyurea anti-corrosion coating. Under an inert atmosphere, isocyanate-based silanes are used to modify graphene oxide, resulting in a modified graphene oxide coating that then forms a polyurea anti-corrosion coating. The resulting coating exhibits strong adhesion to the metal substrate and improves its barrier and corrosion resistance against corrosive media. However, the overall coating preparation process is extremely complex and requires stringent conditions. It not only requires modification of the graphene oxide but also the compounding of bisphenol F epoxy resin and a stabilizing rust-reducing agent to modify the polyurea anti-corrosion coating and enhance its adhesion to the metal substrate. When only isocyanate-based silanes are used to modify graphene oxide, the adhesion is only 9.0 MPa according to GB / T 5210-2006 tests, and its corrosion resistance is limited. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects and shortcomings of existing polyurea coatings and provide a method for preparing a modified graphene oxide-reinforced aspartic acid ester polyurea coating, which can greatly improve the compatibility between fillers and polyurea resin, reduce internal defects in the coating, effectively improve the adhesion between the coating and the metal substrate, and enhance the corrosion resistance of the coating.

[0006] Another object of the present invention is to provide an aspartic acid ester polyurea coating.

[0007] Another objective of this invention is to provide the application of the above-mentioned aspartic acid ester polyurea coating in the preparation of protective materials for marine engineering equipment.

[0008] Another object of the present invention is to provide a coated article comprising a coating formed by curing the above-mentioned polyurea coating, which has good mechanical properties and corrosion resistance.

[0009] The above-mentioned objective of this invention is achieved through the following technical solution:

[0010] This invention protects a method for preparing an aspartic acid ester polyurea coating, comprising the following steps:

[0011] S1, dispersing graphene oxide in a buffer solution, adding dopamine-hydrochloric acid and stirring to react, to obtain polydopamine-modified graphene oxide; the mass ratio of graphene oxide to dopamine-hydrochloric acid is 1:(0.5~3);

[0012] S2, the polydopamine-modified graphene oxide and aspartic acid ester are mixed evenly, and an isocyanate curing agent is added and mixed evenly to obtain an aspartic acid ester polyurea coating.

[0013] In the aspartic acid ester polyurea coating of the present invention, dopamine-hydrochloric acid modified graphene oxide is used as a filler to improve the mechanical properties and corrosion resistance of the coating. Among them, dopamine-hydrochloric acid, as a modifier, can improve the compatibility between graphene oxide nanosheets and polyaspartic acid ester polyurea. At the same time, dopamine undergoes self-polymerization on the surface of graphene oxide to form a polydopamine layer with good adhesion, which can repair the surface defects of graphene oxide nanosheets, improve the density of the coating, prolong the time for corrosive media to reach the metal surface, and also improve the adhesion between the coating and the metal substrate.

[0014] It should be noted that this invention also controls the mass ratio of graphene oxide to dopamine-hydrochloric acid within the range of 1:(0.5-3). This allows for the large-scale coverage and repair of micro-defects in the coating by utilizing the high specific surface area of ​​graphene oxide. Simultaneously, a specific amount of dopamine modification partially reduces the graphene oxide, retaining some organic functional groups on the graphene oxide surface. This synergistic effect with the self-polymerized polydopamine improves compatibility with the polyaspartic acid ester polyurea coating matrix, enhancing the coating's mechanical and corrosion resistance. Furthermore, polydopamine itself possesses a certain corrosion-inhibiting function, providing some corrosion inhibition even in the early stages of coating damage. Insufficient dopamine-hydrochloric acid content leads to incomplete surface modification of graphene oxide, affecting the improvement effect; excessive dopamine-hydrochloric acid causes excessively thick agglomerated filler layers, hindering large-scale coverage and repair of micro-defects in the coating; even worse, it can lead to excessive reduction of graphene oxide to graphene or graphite, altering the physicochemical properties of the filler.

[0015] In some embodiments, in step S1, the buffer solution is a tris(hydroxymethyl)aminomethane buffer solution (Tris) with a pH of 7 to 9.

[0016] In some embodiments, in step S1, the temperature of the stirring reaction is 25–80°C, and the reaction time is 5–32 h.

[0017] In some embodiments, in step S2, the mass ratio of the polydopamine-modified graphene oxide to polyaspartic acid ester is (0.05-0.5):10.

[0018] In some embodiments, in step S2, the amount of the isocyanate curing agent is 65-80 wt.% of the polyaspartic ester. To ensure complete curing of the polyaspartic ester, the curing agent can be used in appropriate excess to achieve room temperature curing, thus increasing the workability of the coating.

[0019] Optionally, the isocyanate curing agent is hexamethylene diisocyanate-based polyisocyanate.

[0020] In some embodiments, in step S2, when the polydopamine-modified graphene oxide and aspartic acid ester are mixed evenly, a diluent is also added, and the mass ratio of the polydopamine ester to the diluent is 10:(3-6).

[0021] In some embodiments, in step S2, the diluent is at least one of butyl acetate, xylene, or propylene glycol methyl ether acetate. The introduction of a diluent can improve the dispersibility of the filler in the resin system and reduce the viscosity of the coating, thus facilitating coating application and leveling.

[0022] This invention protects an aspartic acid ester polyurea coating, which is made by the preparation method of the aspartic acid ester polyurea coating.

[0023] This invention protects the application of an aspartic acid ester polyurea coating in the preparation of protective materials for marine engineering equipment.

[0024] This invention protects a coated article, which is made by applying the aspartic ester polyurea coating at least partially to a metal substrate and curing it to form a coating.

[0025] Optionally, the aspartic acid ester polyurea coating is prepared by coating the aspartic acid ester polyurea coating onto the surface of a metal substrate, and after drying and curing, a polydopamine-modified graphene oxide / polyaspartic acid ester polyurea composite coating is obtained on the surface of the metal substrate.

[0026] Optionally, the metal substrate is at least one of carbon steel, aluminum alloy, titanium alloy, magnesium alloy or copper alloy.

[0027] Optionally, the drying and curing temperature is 25℃~60℃, and the curing time is 24h~72h.

[0028] Optionally, the thickness of the coating is 50–200 μm.

[0029] Compared with the prior art, the beneficial effects of the present invention are:

[0030] This invention provides a method for preparing aspartic acid ester polyurea coating, using dopamine-hydrochloric acid modified graphene oxide as a filler to improve the mechanical properties and corrosion resistance of the coating. Dopamine-hydrochloric acid, as a modifier, enhances the compatibility between graphene oxide nanosheets and polyaspartic acid ester polyurea. Simultaneously, dopamine undergoes self-polymerization on the graphene oxide surface, forming a polydopamine layer with good adhesion. This layer can repair surface defects of the graphene oxide nanosheets, improve coating density, prolong the time it takes for corrosive media to reach the metal surface, and also improve the adhesion between the coating and the metal substrate. Attached Figure Description

[0031] Figure 1The diagram shows the morphological structure of GO-PDA and GO, and the elemental distribution of GO-PDA in Example 1.

[0032] Figure 2 This is a comparison chart of the adhesion of the coatings prepared in Example 1 and Comparative Examples 1-3.

[0033] Figure 3 Electrochemical impedance spectroscopy of the coatings prepared in Example 1 and Comparative Examples 1-2. Detailed Implementation

[0034] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0035] The following examples and comparative examples include the following raw materials:

[0036] Graphene oxide: JCGO-1-50, Nanjing Jicang Nanotechnology Co., Ltd.

[0037] Polyaspartic acid ester: F520, Shenzhen Feiyang Junyan New Material Co., Ltd.

[0038] Curing agent: Hexamethylene diisocyanate-based polyisocyanate, HT-600, Shenzhen Feiyang Junyan New Material Co., Ltd.

[0039] Example 1

[0040] A method for preparing an aspartic acid ester polyurea coating includes the following steps:

[0041] (1) Preparation of polydopamine-modified graphene oxide composite material:

[0042] 0.15 g of graphene oxide was ultrasonically dispersed in 150 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution. The solution was adjusted to pH 8.5 by adding dilute hydrochloric acid dropwise, and then 0.3 g of dopamine-hydrochloric acid was added. The mixture was stirred in a water bath at 60 °C for 24 h on a magnetic stirrer to obtain a black suspension. The suspension was then centrifuged and washed three times with anhydrous ethanol to obtain a black slurry-like polydopamine-modified graphene oxide composite material (GO-PDA).

[0043] (2) Preparation of composite material modified polyaspartic acid ester polyurea:

[0044] Polyaspartic acid ester, GO-PDA and diluent were mixed in a mass ratio of 10:0.17:4.3, wherein the diluent was butyl acetate. After high-speed centrifugation for 3 min, a curing agent accounting for 66.3 wt.% of the mass of the polyaspartic acid ester was added. After high-speed centrifugation for 3 min, a composite material modified polyaspartic acid ester polyurea coating was obtained.

[0045] (3) Coating film layer:

[0046] The composite material modified polyaspartic acid ester polyurea coating obtained in step (2) was coated on the surface of a Q235 carbon steel substrate that had been surface-treated (polished with 60 to 220 mesh abrasive, then ultrasonically cleaned with degreasing solution to remove oil and impurities from the surface, and finally dried in an oven). After drying and curing in an oven at 60°C for 48 hours, a GO-PDA / polyaspartic acid ester polyurea composite coating was obtained on the surface of the Q235 carbon steel. The dry film thickness of the composite coating was 100±10μm.

[0047] Example 2

[0048] A method for preparing an aspartic acid ester polyurea coating includes the following steps:

[0049] (1) Preparation of polydopamine-modified graphene oxide composite material:

[0050] 0.3 g of graphene oxide was ultrasonically dispersed in 200 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution. The solution was adjusted to pH 8.0 by adding dilute hydrochloric acid, and then 0.15 g of dopamine-hydrochloric acid was added. The mixture was stirred in a water bath at 25 °C for 32 h on a magnetic stirrer to obtain a black suspension. The suspension was then centrifuged and washed twice with deionized water and anhydrous ethanol, respectively, to obtain a black slurry-like polydopamine-modified graphene oxide composite material (GO-PDA).

[0051] (2) Preparation of composite material modified polyaspartic acid ester polyurea:

[0052] Polyaspartic acid ester, GO-PDA, and a diluent were mixed in a mass ratio of 10:0.4:5, wherein the diluent was propylene glycol methyl ether acetate. After high-speed centrifugation for 5 minutes, a curing agent accounting for 69.7 wt.% of the mass of the polyaspartic acid ester was added, and after high-speed centrifugation for 5 minutes, a composite material modified polyaspartic acid ester polyurea coating was obtained.

[0053] (3) Coating film layer:

[0054] The composite material modified polyaspartic acid ester polyurea coating obtained in step (2) was coated on the surface of the surface-treated aluminum alloy substrate and dried and cured in an oven at 60°C for 48 hours. Thus, a GO-PDA / polyaspartic acid ester polyurea composite coating was obtained on the aluminum alloy surface. The dry film thickness of the composite coating was 80±5μm.

[0055] Example 3

[0056] A method for preparing an aspartic acid ester polyurea coating includes the following steps:

[0057] (1) Preparation of polydopamine-modified graphene oxide composite material:

[0058] 0.15 g of graphene oxide was ultrasonically dispersed in 120 mL of 10 mM tris(hydroxymethyl)aminomethane buffer solution. The solution was adjusted to pH 9.0 by adding dilute hydrochloric acid, and then 0.45 g of dopamine-hydrochloric acid was added. The mixture was stirred in an 80 °C water bath for 18 h on a magnetic stirrer to obtain a black suspension. The suspension was then centrifuged and washed four times with anhydrous ethanol to obtain a black slurry-like polydopamine-modified graphene oxide composite material (GO-PDA).

[0059] (2) Preparation of composite material modified polyaspartic acid ester polyurea:

[0060] Polyaspartic acid ester, GO-PDA, and a diluent (xylene) were mixed in a mass ratio of 10:0.5:6. After high-speed centrifugation for 4 minutes, a curing agent accounting for 75 wt.% of the mass of the polyaspartic acid ester was added, and the mixture was centrifuged for 5 minutes to obtain a composite material modified polyaspartic acid ester polyurea coating.

[0061] (3) Coating film layer:

[0062] The composite material modified polyaspartic acid ester polyurea coating obtained in step (2) was coated on the surface of the surface-treated aluminum alloy substrate. After drying and curing in an oven at 60°C for 48 hours, a GO-PDA / polyaspartic acid ester polyurea composite coating was obtained on the aluminum alloy surface. The dry film thickness of the composite coating was 120±10μm.

[0063] Comparative Example 1

[0064] A method for preparing a polyaspartic acid ester polyurea coating, which differs from Example 1 in that: this comparative example does not include polydopamine-modified graphene oxide, and specifically includes the following steps:

[0065] (1) Preparation of polyaspartic acid ester polyurea coating:

[0066] A polyaspartic acid ester and a diluent with a mass ratio of 10:4.3 were mixed, wherein the diluent was propylene glycol methyl ether acetate. After high-speed centrifugation for 3 minutes, a curing agent accounting for 66.3 wt.% of the mass of the polyaspartic acid ester was added, and after high-speed centrifugation for 3 minutes, a polyaspartic acid ester polyurea coating was obtained.

[0067] (2) Coating film layer:

[0068] The polyaspartic acid ester polyurea coating obtained in step (1) was applied to the surface of a Q235 carbon steel substrate that had been surface-treated (polished from 60 mesh to 220 mesh, then ultrasonically cleaned with degreasing solution to remove surface oil and impurities, and finally dried in an oven). After drying and curing in an oven at 60°C for 48 hours, a polyaspartic acid ester polyurea coating was obtained on the surface of the Q235 carbon steel. The dry film thickness of the coating was 100±10μm.

[0069] Comparative Example 2

[0070] A method for preparing a polyaspartic ester polyurea coating, differing from Example 1 in that: unmodified graphene oxide is added to the polyaspartic ester polyurea of ​​this comparative example, specifically including the following steps:

[0071] (1) Preparation of polyaspartic acid ester polyurea coating:

[0072] Polyaspartic acid ester, GO and diluent were mixed in a mass ratio of 10:0.17:4.3, wherein the diluent was propylene glycol methyl ether acetate. After high-speed centrifugation for 3 min, a curing agent accounting for 66.3 wt.% of the mass of the polyaspartic acid ester was added. After high-speed centrifugation for 3 min, the modified polyaspartic acid ester polyurea coating was obtained.

[0073] (2) Coating film layer:

[0074] The modified polyaspartic acid ester polyurea coating obtained in step (1) was applied to the surface of a Q235 carbon steel substrate that had been surface-treated (polished from 60 mesh to 220 mesh, then ultrasonically cleaned with degreasing solution to remove oil and impurities from the surface, and finally dried in an oven). After drying and curing in an oven at 60°C for 48 hours, a GO / polyaspartic acid ester polyurea composite coating was obtained on the surface of the Q235 carbon steel. The dry film thickness of the composite coating was 100±10μm.

[0075] Comparative Example 3

[0076] A method for preparing a polyaspartic acid ester polyurea coating differs from Example 1 in that: this comparative example uses silane-modified graphene oxide, specifically including the following steps:

[0077] (1) Preparation of silane-modified graphene oxide

[0078] 0.15 g of graphene oxide was ultrasonically dispersed in 150 mL of deionized water. Deionized water and anhydrous ethanol were mixed at a volume ratio of 1:4 to obtain a 200 mL solution. The pH of the solution was adjusted to 3 with 0.5 mol / L oxalic acid solution, and then 1 g of a 5% (volume fraction) silane coupling agent (KH-550) was added. The mixture was stirred in a 35°C water bath for 2 h to hydrolyze the solution. The hydrolyzed silane coupling agent solution was added to the well-dispersed graphene oxide dispersion, and the reaction was carried out with stirring in a 65°C water bath for 12 h. The mixture was then centrifuged, and washed three times with anhydrous ethanol to obtain silane-modified graphene oxide.

[0079] (2) Preparation of polyaspartic acid ester polyurea:

[0080] Polyaspartic acid ester, silane-modified graphene oxide, and a diluent were mixed in a mass ratio of 10:0.17:4.3, wherein the diluent was propylene glycol methyl ether acetate. After high-speed centrifugation for 3 minutes, a curing agent accounting for 66.3 wt.% of the mass of the polyaspartic acid ester was added, and after high-speed centrifugation for 3 minutes, a composite material modified polyaspartic acid ester polyurea coating was obtained.

[0081] (3) Coating film layer:

[0082] The polyaspartic acid ester polyurea coating obtained in step (2) was applied to the surface of a Q235 carbon steel substrate that had been surface-treated (polished from 60 mesh to 220 mesh, then ultrasonically cleaned with degreasing solution to remove oil and impurities from the surface, and finally dried in an oven). After drying and curing in an oven at 60°C for 48 hours, a silane-modified graphene oxide / polyaspartic acid ester polyurea composite coating was obtained on the surface of the Q235 carbon steel. The dry film thickness of the composite coating was 100±10μm.

[0083] Performance testing

[0084] Example 1 and Comparative Examples 1-3 were characterized and tested as follows:

[0085] 1. Microstructure testing of composite materials

[0086] The prepared graphene oxide and GO-PDA were observed under a scanning electron microscope, and the morphology, structure, and elemental distribution were obtained as follows: Figure 1 As shown, PDA achieves uniform growth on the surface of graphene oxide, which reduces the aggregation and wrinkles of the graphene oxide itself.

[0087] 2. Coating adhesion test

[0088] The coatings prepared in Example 1 and Comparative Examples 1-3 were subjected to adhesion tests using a pull-out tester, and the results are as follows: Figure 2 As shown.

[0089] The results show that the adhesion of the GO-PDA / polyaspartic acid ester polyurea coating in Example 1 of the present invention reaches 16.5 MPa, while the adhesion of the polyaspartic acid ester polyurea composite coating in Comparative Example 1 without the addition of polydopamine-modified graphene oxide composite material is 9.23 MPa, the adhesion of the polyaspartic acid ester polyurea coating in Comparative Example 2 with the addition of unmodified graphene oxide is 11.38 MPa, and the adhesion of the polyaspartic acid ester polyurea coating in Comparative Example 3 using silane-modified graphene oxide is 11.97 MPa.

[0090] 3. Electrochemical impedance spectroscopy experiment of the coating

[0091] The coatings prepared in Example 1, Comparative Example 1, and Comparative Example 2 were immersed in a 3.5 wt.% sodium chloride solution and subjected to electrochemical testing. After 100 days of electrochemical testing, the impedance modulus results are as follows: Figure 3 As shown.

[0092] The results show that the low-frequency impedance modulus of Embodiment 1 of the present invention is consistently maintained at 10. 11 Ω·cm 2 The low-frequency impedance modulus of Comparative Example 1 always changes from 10. 10 It dropped to 10 9 Ω·cm 2 The low-frequency impedance modulus of Comparative Example 2 only remained at 10. 10 Ω·cm 2 This demonstrates that the polyaspartic acid ester polyurea composite material modified with polydopamine of the present invention can enhance the physical barrier properties of the coating and improve its long-term corrosion resistance.

[0093] The above embodiments of the present invention are merely examples for clearly illustrating the present invention and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A product coated with polyaspartic acid ester polyurea, characterized in that, It is made by applying at least partially a polyaspartic ester polyurea coating to a metal substrate and curing it to form a coating; The preparation method of the polyaspartic acid ester polyurea coating includes the following steps: S1, dispersing graphene oxide in a buffer solution, adding dopamine-hydrochloric acid and stirring to react, to obtain polydopamine-modified graphene oxide; the mass ratio of graphene oxide to dopamine-hydrochloric acid is 1:(2~3); S2, the polydopamine-modified graphene oxide, polyaspartic acid ester, and diluent are mixed evenly, and an isocyanate curing agent is added and mixed evenly to obtain a polyaspartic acid ester polyurea coating; the mass ratio of polydopamine-modified graphene oxide to polyaspartic acid ester is (0.05~0.5):10; the mass ratio of polyaspartic acid ester to diluent is 10:(3~6); The isocyanate curing agent is hexamethylene diisocyanate-based polyisocyanate; In step S2, the amount of the isocyanate curing agent is 65-80 wt. of polyaspartic acid ester.

2. The article according to claim 1, characterized in that, In step S1, the buffer solution is a tris(hydroxymethyl)aminomethane buffer solution with a pH value of 7-9.

3. The article according to claim 1, characterized in that, In step S1, the temperature of the stirring reaction is 25~80℃, and the reaction time is 5~32h.

4. The article according to claim 1, characterized in that, In step S2, the diluent is at least one of butyl acetate, xylene, or propylene glycol methyl ether acetate.